Determinants of Organizational Commitment in Emerging Market: Korean Expatriates in India - Kim, Hyeong-Deug (European Journal of Economics and Business Studies, 2019)
This study examined expatriates’ organizational commitment by focusing on how willingness to accept an international assignment, training for an international assignment, expatriate empowerment, perceived organizational support, and demographic variables in order to predict the Korean expatriates’ organizational commitment in India. The results provided empirical evidence that expatriates are more committed to their organization when they perceived organizational support and empowerment and gave some valuable insights to develop relevant training for cultural adjustment and managerial skill development as well as supporting programs, especially for growing companies in emerging economies. By building on the cross-cultural management and organizational theories and researches, this study expands these recent findings to expatriate studies.
Keywords: commitment, empowerment, expatriates, international assignments, perceived organizational support